2007
DOI: 10.1007/s12032-007-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline and alpha-tocopherol in prevention of radiation-induced lung toxicity in patients with lung cancer

Abstract: Combined use of pentoxifylline and vitamin E is reported to reduce radiation-induced toxicity in normal tissues at molecular level. We plan to evaluate the role of combined use of pentoxifylline (PTX) and alpha-tocopherol (vitamin E; Vit E) for minimizing radiation-induced lung toxicity. A total of 91 lung cancer patients were randomized. Among them, 44 received PTX (400 mg three times a day orally and Vit E 300 mg twice a day orally during the entire period of radiotherapy. PTX and Vit E were further administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Recently, PTX has been of interest in radiation oncology based on its reported potential ability to ameliorate radiation-and chemotherapy-induced toxicity [13][14][15][16][17]. PTX has been shown to enhance microvascular blood flow and decrease platelet aggregation, thereby maintaining perfusion in radiated tissues [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PTX has been of interest in radiation oncology based on its reported potential ability to ameliorate radiation-and chemotherapy-induced toxicity [13][14][15][16][17]. PTX has been shown to enhance microvascular blood flow and decrease platelet aggregation, thereby maintaining perfusion in radiated tissues [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PTX has been of interest in radiation oncology for the improvement of tumor perfusion and tumor oxygenation [9][10][11][12]. In several clinical and experimental studies, PTX was also shown to diminish the severity of late radiation injury, however, it remains to be shown whether PTX is beneficial in the prevention of early radiation injury [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in another study, it was revealed that the use of only pentoxifylline decreased lung toxicity secondary to radiation in both the early stage and late stage. Especially in cases simultaneously exposed to chemoradiotherapy, which increases the risk for toxicity, it is specified that vitamin E and pentoxifylline can be used (81,82). It is thought that understanding the mechanism based on cytokine in radiation-induced lung injury can be solution options for treatment.…”
Section: Prevention Of Lung Injury Associated With Radiationmentioning
confidence: 99%
“…Eighteen patients who continued on PTX-vitamin E for 6 months had a 72% (±15%) reduction in surface area. Misirlioglu et al (2007) evaluated the radioprotective benefit of PTX-vitamin E in lung cancer patients receiving thoracic irradiation. Forty-four patients received 400 mg PTX three times per day and vitamin E 300 mg twice per day during the course of radiation therapy and thereafter for 3 months.…”
Section: Pentoxifylline and α-Tocopherolmentioning
confidence: 99%